Eksistensi Hak Ulayat dalam Pembangunan Daerah - mudjiono mudjiono (Jurnal Hukum IUS QUIA IUSTUM, 2004)
The existence of ulayat right is considered as an inhibiting factor of a development plan. Conflict of interest occurred between the owner and the user of the land because of the exploitation of ulayat land, needs to settle immediately based on win-win-sollution principle.